2017
DOI: 10.15406/jcpcr.2017.07.00241
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Breast Cancer Awareness Level among Saudi Medical Students

Abstract: Objective: To assess the levels of breast cancer related knowledge among Saudi medical students.Methodology: This is a cross sectional survey conducted in three medical colleges at university of Hail, Kingdom of Saudi Arabia (KSA). About 254 medical students have participated in the survey. Results:On asking participants about their existing level of knowledge regarding breast cancer, 55/254(21.6%), 102/254(40%), 85/254(33.4%) and 12/254(5%) of the participants indicated very good, good, poor and know nothing,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 21 publications
0
0
0
Order By: Relevance
“…Alsowiyan A et al used the same tool to assess the knowledge as we did, and the authors reported that 38.9% of women had poor knowledge about BC, while only 61% had adequate knowledge [ 13 ]. This is consistent with the results from other studies including that of Habib et al, who reported that 34% of the university students had poor knowledge regarding BC [ 15 ], and that of Ahmed et al, who reported that among 254 medical students, 33.4 had poor knowledge regarding BC [ 16 ]. In another study conducted in the eastern region of Saudi Arabia, the authors reported that 29.3% of the Saudi female population had a low level of knowledge about BC [ 17 ], and a second study showed that 23.6% of female students in the central region of Saudi Arabia had low knowledge [ 18 ].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Alsowiyan A et al used the same tool to assess the knowledge as we did, and the authors reported that 38.9% of women had poor knowledge about BC, while only 61% had adequate knowledge [ 13 ]. This is consistent with the results from other studies including that of Habib et al, who reported that 34% of the university students had poor knowledge regarding BC [ 15 ], and that of Ahmed et al, who reported that among 254 medical students, 33.4 had poor knowledge regarding BC [ 16 ]. In another study conducted in the eastern region of Saudi Arabia, the authors reported that 29.3% of the Saudi female population had a low level of knowledge about BC [ 17 ], and a second study showed that 23.6% of female students in the central region of Saudi Arabia had low knowledge [ 18 ].…”
Section: Discussionsupporting
confidence: 92%
“…and that of Ahmed et al, who reported that among 254 medical students, 33.4 had poor knowledge regarding BC [16]. In another study conducted in the eastern region of Saudi Arabia, the authors reported that 29.3% of the Saudi female population had a low level of knowledge about BC [17], and a second study showed that 23.6% of female students in the central region of Saudi Arabia had low knowledge [18].…”
Section: Discussionmentioning
confidence: 88%
“…15 " They discovered that 34% of the 301 students who were participating had inadequate knowledge. Ahmed et al 24 Support the results of this study. Their investigation evaluated the Breast cancer awareness level among Saudi medical students and discovered that 33.4% of the 254 students had an inadequate understanding.…”
Section: Discussionsupporting
confidence: 87%